2014
DOI: 10.1371/journal.pone.0091703
|View full text |Cite
|
Sign up to set email alerts
|

relA Enhances the Adherence of Enteropathogenic Escherichia coli

Abstract: Enteropathogenic Escherichia coli (EPEC) is a known causative agent of diarrhea in children. In the process of colonization of the small intestine, EPEC synthesizes two types of adhesins, the bundle-forming pilus (BFP) and intimin. The BFP pilus is an adhesin associated with the initial stages of adherence of EPEC to epithelial cells, while the outer membrane protein intimin carries out the intimate adherence that takes place at the third stage of infection. BFP is encoded by the bfp operon located in plasmid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…The interaction network diagram of Vvrr1 with its potential target genes shows some of the target genes with their virulence function. For example, relA has been proved to enhance the adhesion of E. coli to host cells [58]. katG can increase the survival and escape rates of Aeromonas hydrophila in fish macrophages [59].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction network diagram of Vvrr1 with its potential target genes shows some of the target genes with their virulence function. For example, relA has been proved to enhance the adhesion of E. coli to host cells [58]. katG can increase the survival and escape rates of Aeromonas hydrophila in fish macrophages [59].…”
Section: Discussionmentioning
confidence: 99%
“…ppGpp is positively associated with bacterial virulence in several species [8]. In E. coli pathotypes, such as EHEC, UPEC and EPEC ppGpp modulates the expression of virulence factors, such as the synthesis of adhesins and fimbriae important for bacterial attachment to the host cell [1214]. However, it has been shown that ppGpp inhibits the lytic development and DNA replication of Stx bacteriophages, which suggests a negative role for ppGpp in the expression of virulence in bacteria that carry toxin-encoding phages such as STEC [1517].…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies suggested that the bundle-forming pilus (Bfp) participates in the initial intestinal interaction, but later experiments demonstrated that Bfp stabilizes microcolony formation (24). Recent studies suggested that the E. coli common pilus (ECP) and the product of the relA gene contribute to the interaction of EPEC with host epithelial cells (25,26); however, additional experiments are required to confirm the roles of these adhesins in vivo. Here, we mainly discuss the roles of H-NS-regulated products and Lpf in adhesion and colonization of the intestinal tract.…”
Section: Discussionmentioning
confidence: 99%